Odyssey Self Reflection - Saving money / Faculty of Art and Design UiTM Cawangan Sarawak - Mohd Rathi, Mohd Razif (Perpustakaan Tun Abdul Razak, PTAR Universiti Teknologi Mara Cawangan Sarawak, 2021)
The inner experience had inspired me to create artworks which consisted of drawing, painting, printmaking and sculpture. The concept of my artworks told a story of my habit that I have routinized ever since I was little, which pertained to saving up money to buy school-related materials. I also inserted the elements and principles of asymmetry in my painting, in addition to focusing on organic and geometrical forms in my drawing.